G388 "Itchy-Sneezy-Wheezy" Survey: Comparison of GP referral reasons to diagnoses on first allergy clinic letters. (7th April 2014) - Taha, S; Patel, N; Gore, C
Abstract : Aims: Allergic disease is common: 25% of patients registered in General Practice (GP) are affected, and 11% have multiple allergic conditions. We previously found that only 7% of GP referral letters to paediatric allergy services reflected complexity of allergic disease, leaving many children undertreated. Following the implementation of the RCPCH Allergy Care Pathways as part of the Itchy-Sneezy-Wheezy Project from 2010 (www.itchysneezywheezy.co.uk ), we hypothesised, that local referral practice may have changed. Methods: Retrospective survey of 100 successive GP referral letters to a paediatric allergy clinic between March and August 2013, recording referral reason, pre-/co-existing allergic diagnoses, and any treatment offered. Findings from the first clinic letter also reviewed, diagnoses and treatments recorded. Comparison between referral and first clinic letter. Results: Overall, 106 main referral reasons were identified in 100 letters. Referral reasons included: Food allergy (55/100; 55%), eczema (16%), other allergy (11%), rash (8%), urticaria (4%), asthma (2%), allergic rhinitis (2%) and gastrointestinal problems (2%). GP referral letters suggested that 63% of patients had one allergic condition, 29% had two, 7% had three and 1% had more than three allergic conditions. At first allergy assessment diagnoses included: Food allergy (71% vs. 55% mentioned in GP referral letter), eczema (57% vs. 16%), allergic rhinitis (30% vs. 2%), asthma (15% vs. 2%), gastrointestinal problems (20% vs. 2%) and other allergy (40% vs. 11%); non-allergic findings 13% vs 1%. Higher disease complexity was found in clinic: Only 21% of patients had one, 25% had two, 33% had three and 21% had >3 allergic conditions. Multiple food allergies were diagnosed in 49/100 (49%); 32/49 had ≥3 food allergies. Conditions appeared undertreated prior to referral, with 56% of patients not having received treatment (13% left clinic without medication). Overall analysis indicated that 31% of GP referral letters reflected complexity of allergic disease, whereas 69% did not. Conclusion: Compared with previous results, allergic co-morbidities are better recognised but conditions still appear undertreated (based on information given in referral letters and medication prescribed from clinic). The improved local training and awareness following the Itchy-Sneezy-Wheezy Project may have resulted in this benefit, but more awareness and training are required.